2017
DOI: 10.1016/j.eurpsy.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Age at the time of onset of psychosis: A marker of specific needs rather than a determinant of outcome?

Abstract: Background: While there is suggestion that early onset of psychosis is a determinant of outcome, knowledge regarding correlates of later onset age is more limited. This study explores the characteristics of patients developing psychosis after age 26, towards the end of the usual age range of early intervention programs, in order to identify potential specific needs of such patients.Methods: 256 early psychosis patients aged 18-35 were followed-up prospectively over 36 months. Patients with onset after 26 ("lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
3
1
0
Order By: Relevance
“…In line with findings reported in other Italian comparable studies (Cocchi et al, ; Ruggeri et al, ), compared with UHR− and UHR+, FEP patients assessed in the ReARMS protocol showed significantly higher mean age at entry and a preponderance of males. These results confirm the well‐known earlier onset of psychosis in males, especially in early adulthood (Golay et al, ). Differently, UHR mental states occurred more frequently in adolescence, hence the importance of overcoming the child‐adult service gap and implementing reformed service models that are not strictly aligned to chronology and rigid diagnostic boundaries (Raballo et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…In line with findings reported in other Italian comparable studies (Cocchi et al, ; Ruggeri et al, ), compared with UHR− and UHR+, FEP patients assessed in the ReARMS protocol showed significantly higher mean age at entry and a preponderance of males. These results confirm the well‐known earlier onset of psychosis in males, especially in early adulthood (Golay et al, ). Differently, UHR mental states occurred more frequently in adolescence, hence the importance of overcoming the child‐adult service gap and implementing reformed service models that are not strictly aligned to chronology and rigid diagnostic boundaries (Raballo et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Consistently with findings reported in ‘Programma 2000’ study (Cocchi et al, 2008, 2013; Cocchi, Cavicchini, et al, 2015b), patients with FEP entered the Pr‐EP programme showed a preponderance of males, confirming literature's data about the prevalence of FEP onset in adult males (Golay et al, 2017). Moreover, at baseline our participants were frequently unemployed, unmarried and living with parents in their family of origin, showing a poorer socio‐occupational functioning.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, only 56% of patients in the group with later onset returned to their premorbid functioning, and only 24% returned to work at discharge. This is in line with previous findings (Golay et al, 2017) showing that bringing patients back to work is challenging despite employment before psychosis onset, suggesting specific strategies are needed to protect competencies patients acquired before the disorder emerges.…”
Section: Discussionsupporting
confidence: 92%